HIV Risk Perception among HIV Negative or Status-Unknown Men Who Have Sex with Men in China. (30th March 2014) - Fan, Wensheng; Yin, Lu; Qian, Han-Zhu; Li, Dongliang; Shao, Yiming; Vermund, Sten H.; Ruan, Yuhua; Zhang, Zheng
Abstract : Objective. To evaluate HIV risk perception and its associated factors among Chinese MSM. Methods. A cross-sectional study was conducted among MSM with an HIV negative or unknown status in Beijing, China, between 2011 and 2012. A questionnaire interview was conducted and a blood sample was collected for HIV and syphilis testing. Results. Of 887 MSM who reported they were HIV negative or did not know their HIV status before recruitment, only 7.3% reported a high risk of HIV infection, 28.0% medium risk, 52.2% low risk, and 12.5% no risk. In multivariate logistic regression models using those who reported a medium self-perceived risk as a reference group, self-reported high risk of HIV perception was associated with minority ethnicity (odds ratio [OR]: 2.91; 95% confidence interval [CI]: 1.03–8.19), self-reported history of sexually transmitted diseases (OR: 2.27; 95% CI: 1.25–4.10), and HIV testing times since the last HIV testing (OR: 0.47; 95% CI: 0.26–0.84); low self-perceived risk of HIV infection was related to full-time employment (OR: 1.58; 95% CI: 1.15–2.18) and illicit drug use (OR: 0.28; 95% CI: 0.10–0.75). Conclusions. The HIV/AIDS epidemic is rapidly rising among Beijing MSM, but more than half MSM did not perceive this risk.